2019
DOI: 10.1111/ijn.12812
|View full text |Cite
|
Sign up to set email alerts
|

Nurse staffing models in medical‐surgical units of acute care settings: A cross‐sectional study

Abstract: Background: Nurse staffing models have been developed across different countries to address nursing shortages and improve quality of nursing care. However, there is no published study that describes nurse staffing models in Ethiopian hospitals. Aims:To describe the existing staffing models for nursing practice in acute care units of two hospitals (one public and one private) in Ethiopia. Methods:A cross-sectional study was conducted from July to December 2018. A self-administered questionnaire was used to coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…There were no significant variations in relation to age, gender, educational status and years of work experience of the participants in TP1 and TP2. The sociodemographic characteristics of participant nurses during TP1 are presented elsewhere (Assaye et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were no significant variations in relation to age, gender, educational status and years of work experience of the participants in TP1 and TP2. The sociodemographic characteristics of participant nurses during TP1 are presented elsewhere (Assaye et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Data on nurse‐to‐patient ratio in acute care settings in Ethiopia are scarce. Our previous research showed that the average nurse‐to‐patient ratio in medical‐surgical acute care units of the public hospital ranges from 1:7 to 1:27 across different units and shifts (Assaye et al, 2020). More than half of the nurses who worked in the units and participated in the study reported that they worked 6 or 7 days per week, with an overall average of 50 h worked per week (Assaye et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These were all labour-related reasons and included inadequate numbers of nurses and nurse assistive personnel and an unexpected rise in patient care numbers. Although the smaller numbers limit generalizability, they speak to the importance of poor staff to patient ratios in many LMIC; in the more resource constrained settings ratios have been reported to be as extreme as 1 nurse caring for around 25 patients [27,69]. Studies that investigate the role nurse staffing plays in missed nursing care within these environments would be helpful.…”
Section: Discussionmentioning
confidence: 99%
“…The evolution and the evidence for nurse staffing in low/middle-income countries (LMICs) are less clear. In more resource-challenged LMIC settings, nurse staffing ratios might be as low as 1 nurse caring for over 25 patients on a shift 22 23. For such settings, the WHO has promoted the Workload Indicator Staffing Needs (WISN) planning tool which relies on data from health information systems 24.…”
Section: Introductionmentioning
confidence: 99%